A case–case study comparing the individual risk factors and symptomatology of Salmonella Heidelberg and Salmonella Typhimurium in Ontario in 2015, following implementation of the Ontario Investigation Tools. (4th May 2020) - Paphitis, Katherine; Pearl, David L.; Berke, Olaf; McEwen, Scott A.; Trotz‐Williams, Lise
Abstract: Salmonella Heidelberg and Salmonella Typhimurium are among the most common serotypes responsible for human salmonellosis in Ontario. Introduction of the Ontario Investigation Tools (OIT) in 2014 allowed for standardized case investigation and reporting. This study compared the risk factors and symptomatology for sporadic S . Heidelberg and S . Typhimurium cases reported in Ontario in 2015, following implementation of the OIT. Multilevel logistic regression models were applied to assess associations between serotype and individual‐level demographic characteristics, exposures and symptoms for sporadic confirmed cases of S . Heidelberg and S . Typhimurium in Ontario in 2015. There were 476 sporadic cases of S . Typhimurium ( n  = 278) and S . Heidelberg ( n  = 198) reported in Ontario in 2015. There were significant associations between the odds of the isolate from a case being one of these serotypes, and travel, consumption of sprouts (any type), contact with reptiles and development of malaise, fever or bloody diarrhoea. The S . Typhimurium and S . Heidelberg cases differed in both symptom presentation and risk factors for illness. Case–case comparisons of Salmonella serotypes have some advantages over case–control studies in that these are less susceptible to selection and recall bias while allowing for rapid comparison of cases to identify potential high‐risk exposures that are unique to one of the serotypes when compared to the other. Comparing cases of two different Salmonella serotypes can help to highlight risk factors that may be uniquely associated with one serotype, or more strongly associated with one serotype compared to another. This information may be useful for understanding relative source attribution between common serotypes of Salmonella .